Using gelatin dactyloscopic foils and computer program Adobe Photoshop in expert analysis of crossed lines - Busarčević, Miroslav; Simonović, Branislav (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
This paper presents the method of crossed lines expert analysis developed and applied in Serbia and other countries in the region by Miroslav Busarčević, a court expert with a degree in physical chemistry and MSc in criminalistics. The authors of the paper explain the procedure of lifting the prints of crossed lines using gelatin dactyloscopic foils, the scanning and visualization of the obtained print in the Adobe Photoshop computer program; presentation and interpretation of the results.
Keywords: Photoshop; techniki liftingu; folie daktyloskopijne żelatynowe; skrzyżowane linie